Social Media Influence on the Language Varieties of Adolescents - Saptiana Sulastri; Dela Meila Sari; Rizna Tri Atikah; Theodora Karina (Darul Ilmi Bina Insan Foundation, 2026)
The widespread use of social media has transformed adolescents’ communication practices by encouraging the emergence of diverse language varieties in digital interactions. This study aims to describe the language varieties used by adolescents in social media communication and identify the dominant forms of language employed across digital platforms. A quantitative descriptive research design was employed involving 30 adolescents aged 13–18 years who actively used Instagram, WhatsApp, and TikTok. Participants were selected through purposive sampling, while linguistic data were collected through structured observation and documentation of comments, captions, status updates, and instant messages. The data were classified into four language categories slang, abbreviations, code-mixing, and formal language and analyzed using descriptive statistics. The findings revealed that slang was the most frequently used language variety (40%), followed by abbreviations (25%), code-mixing (20%), and formal language (15%). These results indicate that adolescents predominantly use informal and expressive language in digital communication while adapting their language choices to online interaction contexts. This study contributes to the field of digital sociolinguistics by providing quantitative evidence on the distribution of adolescent language varieties across multiple social media platforms and offers insights for educators to promote context-appropriate language use in both digital and formal communication.